Digitalisasi Rantai Pasok Terhadap Kinerja Perusahaan Yang Dimediasi Integrasi Internal - Widowati, Dorina; Darasih, Ratna; Danya Ibrahim, Harsha (GEMA EKONOMI, 2023)
The purpose of this study is to analyze supply chain digitalization of company performance mediated by internal integration. The research method uses the SEM method. The number of data samples taken by 105 SME owners in East Jakarta, Bekasi and West Java using Google forms. The design of this study is a hypothesis testing research using survey methods. Hypothesis testing research or called analytical and predictive. The results of his research There is a positive influence of Supply Chain Digitalization on Company Performance, There is a positive influence of Supply Chain Digitalization on Internal Supply Chain Integration, There is a positive influence of Supply Chain Internal Integration on Company Performance, There is a positive influence of Supply Chain Digitalization on Company Performance through Internal Supply Chain Integration